ISOTOPIC SYSTEMS AND STIRRING TIMES OF THE EARTHS MANTLE - Allegre C.J.; Lewin E. (My University, 1995)
We have developed a simple model which describes the evolution of isotopic and chemical heterogeneities of radiogenic systems in a reservoir undergoing differentiation, input and convection. We demonstrate that for parent-daughter isochron diagrams, such as those for mantle materials, the slope of the correlation line gives the approximate stirring time, defined as the characteristic time of homogenisation due to convection. In the case of the lead-lead isotopic diagram (207Pb204Pb vs.206Pb204Pb ) the slope of the correlation corresponds to an age of the order of twice the stirring time. We then constrain the stirring time of the whole upper mantle at around 0.9 Ga, and that for the MORB source reservoir alone at about 220 Ma.